Meninjau Efektivitas Program Bantuan Pangan Non Tunai (BPNT) di Desa Sailus, Liukang Tangaya, Pangkajene dan Kepulauan - Zainuddin, Muhlis; Novrayanti Salman, Rara (AhInstitute of Research and Community Service (LP2M) Institute of Social Sciences and Business Andi Sapada, 2023)
This type of research is quantitative research changed to qualitative and research type using a descriptive analysis approach that aims to determine how effective the implementation of the non-cash food assistance program (BPNT) in Sailus Village, Liukang Tangaya District, Pangkajene Regency and Islands. The data collected consisted of observations and interviews. based on observations made. The population in this study is the village and community apparatus. The results of the research on the Effectiveness of the Implementation of the Non-Cash Food Assistance Program (BPNT) in Sailus Village, Liukang Tangaya District, Pangkajene Regency and Islands based on 5 (five) indicators proposed by Sutrisno Year (2007), namely Program Understanding, Right on Target, On Time, Achieving Goals, and Real Change. It can be concluded that it has not been effective. Because of the 5 (five) indicators above, only program management can be said to be effective, while the other 4 (four) indicators have not been said to be effective.